Efficacy of Homoeopathic medicine in treating cases of Upper Respiratory Tract Infections - Dr Prashant Chavan M.D. (Hom); Dr. Neeta Chavan (Revista Electronica de Veterinaria, 2024)
In the rainy season, the common diseases are Upper respiratory tract infections (URTIs). Specific homeopathic remedies are very influential among children in conditions of URTIs. Homeopathic remedies also help improve immunity, reducing the intensity and frequency of attacks of infections of URTIs. This information will benefit many children who suffer from diseases of the Upper Respiratory Tract.